ANALISIS PENETAPAN HARGA SEMBAKO DALAM MENINGKATKAN DAYA BELI MASYARAKAT PADA UD. LUSI KECAMATAN HILIDUHO KABUPATEN NIAS - Mendrofa, Sepriani; Harefa, Idarni; Mendrofa, Yupiter; Laia, Otanius (Jurnal Suluh Pendidikan, 2025)
The purpose of pricing by a company is to Survive, Maximize Profit, Sales Mechanism, Prisetise, Development on Investment (ROI), Odd Price. This research uses descriptive qualitative, which analyzes comparisons based on data and information in the form of oral sentences obtained from the object of research, then draws research conclusions based on the data and information obtained. Respondents in this study, namely: UD shop owner. Lusi, UD shop employees. Lusi, and customers at UD stores. Lusi Hiliduho District, Nias Regency. The results of the study state that the determination of basic food prices at UD. Lusi Hiliduho District, Nias Regency is carried out by considering the cost of shipping goods from Gunungsitoli to Hiliduho, the desired profit percentage, analyzing prices from competitors. UD. Lusi Hiliduho District, Nias Regency takes a maximum profit of 10% of the original price of goods.